Behaviour of Palm Olein During Low Temperature Storage and Identification of Palm Olein Cloud - Phyo, Zaw Swe (1994)
Palm olein, one of the world's most consumable oil, faces problems such as poor low temperature stability and formation of cloud upon storage. In order to study the behaviour of the oil during low temperature storage and identify the components of cloud, the oil was crystallized at 12.5°C over the period of 12 to 24 hours. The behaviour of the triglycerides present in the crystallized oil were monitored by three independent analyses: carbon number analysis (CN) by gas liquid chromatography (GLC) , fatty acid composition and content by fatty acid methyl esters (FAME)-GLC, and glyceride composition and content by reverse phase high performance liquid chromatography (RP-HPLC). At 18 hours of storage, the triglyceride types determined by CN analysis that hadthe maximum concentration (44.49%) was C50 while C52 exhibited the lowest value of 41.10%. In FAME analysis, palmitic acid (C16) had the highest concentration of 41.67% after the oil had been stored for 15 hours while oleic (C18:1) exhibited the lowest value of 41.52%. Triglyceride analysis by HPLC showed that palmitic-oleic-pal mitic (POP) concentration increased to the highest value of 33.53% at 18 hours of storage while palmitic-oleic-oleic (POO) concentration decreased to the lowest value of 23.98% which represent 19.96% increased and 12.77% decreased, respectively. The second aspect studied was the separation of cloud from palm olein and identification of the glyceride that made up the cloud. The cloud from palm olein was separated from the mother (liquid) oil by crystallizing the oil at 10˚C for 4 hours followed by brief centrifugation . Oils from three different sources were used as samples. Isolated clouds were identified by using the three analyses mentioned above. Clouds from all three sample oils were found to comprise of 1,3-dipalmito-glycerol and I-palmito-3-oleo-glycerol. The physical properties of the cloud was determined by X-ray diffraction (XRD) and differential scanning calorimetry (DSC) analyses. A polarized optical microscope was employed to observe the crystal morphology. The results indicated that the cloud crystals had a mix structure of B-a and B-b polymorphic forms, a melting point of 70. 3°C, crystallization temperature of 53. 8°C, the heat of fusion and crystallization were 129.84J/g and - 129.24J/g respectively. The most common crystal size ranged from 70f.'m to 80f.'m .